Tinjauan Ulang Rancangan Penargetan Negara dan Distribusi Program Perlindungan Sosial - Katiman Kartowinomo (Salus Cultura: Jurnal Pembangunan Manusia dan Kebudayaan, 2021)
The Government of Indonesia has implemented social protection programs (SPPs) to reduce the impact of the economic crisis and continued to implement the programs in the recent pandemic situation. To increase the effectiveness of the program implementation, the state involves local governments and communities both in the targeting process and program delivery. The central government involves a village meeting called musyawarah desa (musdes) to update beneficiary’ data of social protection programs and Basis Data Terpadu (BDT-Unified Database). However, issues of mistargeting in the form of inclusion and exclusion error persist. Using the deliberative democracy framework and ethnographic case study approach, this study seeks to understand why mistargeting continues to occur by assessing the process of the musdes. This study found the problems of a centralized design of targeting in the existing social, power and accountability relations in the village, and suggest the need to consider giving more authority and responsibility to local governments and villages in the targeting process and delivery of the SPPs.